MARKETING MIX FACTORS AFFECTING THE DECISION TO USE THE SERVICE OF TONG SERVICE MOTORCYCLE REPAIR SHOP IN SOI KING KAEW 37 - Rakchang , Jureerat; Visitnitikitja, Chinnaso (Journal of MCU Nakhondhat, 2023)
This study aimed to study 1) the decision to use Tong Motorcycle Repair Services shop in Soi King Kaew 37, 2) a comparison of the decision to use Tong Motorcycle Repair Services shop in Soi King Kaew 37 classified by personal information, and 3) Marketing mix factors affecting the decision to use Tong Motorcycle Repair Services shop in Soi King Kaew 37, the population in the study was those who used motorcycle repair shops. A total of 400 samples were selected, and the statistics used were percentage, means, t - test Fest (One - way ANOVA), and Multiple Regression Analysis. The results of the study showed that most of the respondents were male, aged 31 - 40 years old, employed/employees in private companies. Average income per month 20,001 - 30,000 baht, use Honda Automatic motorcycle brand, Frequency of the services 2 - 5 times/year such as oil change service. Marketing mix factors and the decision to use Tong Motorcycle Repair Service shop were significant. Personal differences such as age, occupation, motorcycle engine system, and the Frequency of using the service per year had different effects on the decision to use the motorcycle repair shop service differently. Product aspects such as price, marketing promotion, personnel, service process, and physical elements influence the decision to use a motorcycle repair shop at the statistically significant level of .05.